Analysis of Students' Problem Solving Ability on Set Material According to Polya Model - Pebriyanti, Yayang; Amelia, Risma (IKIP Siliwangi, 2023)
Students' mathematical problem solving ability is very influential on learning outcomes that can be implemented in everyday life. However, the facts in the field show that students' mathematical problem solving skills are still low. The purpose of this research is to analyze student difficulties in set material in terms of problem solving theory according to Polya's model. The method used is descriptive qualitative, with data obtained through a test instrument of mathematical problem solving ability on set material with the applied subjects, namely 32 seventh grade students from one of the State Junior High Schools in Cipeundeuy District. Based on the results obtained, the students' ability to solve math problems based on polya steps is high. However, there were still some errors in the results of student answers in solving problem solving questions, including: not writing down what was known, what was asked, and not describing these elements, the process of planning problem solving was not systematic, not understanding the problem, errors in internal calculation of answers and conclusions which are not in accordance with the results of the solution.